Analisis Kepuasan Kerja, Disiplin Kerja, Kualitas Kehidupan Kerja dan Keterikatan Kerja Terhadap Kinerja Pegawai pada PT. Kereta Api Indonesia Medan - Ina Marisa Sitepu; Sahat P. Remus Silalahi; Tiur Rajagukguk (Universitas Methodist Indonesia, 2024)
The purpose of this study was to determine and analyze job satisfaction, work discipline, quality of work life, work engagement on the performance of employees of PT. Kereta Api Indonesia Medan. The type of data is quantitative data with a saturated sample of 94 respondents. This study concluded that the variable job satisfaction has a coefficient (B1) = 0.487 with tcount (9.911) > ttable 1.9867 and significant (0.000) <0.05. This shows that the variable of job satisfaction has a positive and significant effect partially on the performance of employees of PT. Medan Indonesian Railways. The work discipline variable has a coefficient (B2) = 0.446 with tcount (24.203) > ttable 1.9867 and significant (0.000) <0.05. This shows that the work discipline variable has a positive and significant effect partially on the performance of employees of PT. Medan Indonesian Railways. The quality of work life variable has a coefficient (B3) = 0.145 with tcount (2.654) > ttable 1.9867 and significant (0.009) <0.05. This shows that the variable of quality of work life has a positive and significant effect partially on the performance of employees of PT. Medan Indonesian Railways. The work engagement variable has a coefficient (B3) = 0.158 with tcount (4.572) > ttable 1.9867 and significant (0.000) <0.05. This shows that the work engagement variable has a positive and significant effect partially on the performance of employees of PT. Medan Indonesian Railways. Fcount is 406.310 with a significance level of 0.000. While Ftable (α = 0.00) is 2.47. Therefore, Fcount (406.310) > Ftable (2.47) and a significance level of 0.000 <0.05 indicates that the independent variables (job satisfaction (X1), work discipline (X2), quality of work life (X3) and work engagement (X4) ) simultaneously has a positive and significant effect on the performance of employees of PT. Medan Indonesian Railways. Adjusted R Square value of 0.946 means 94.6% of PT. Kereta Api Indonesia Medan can be explained by job satisfaction (X1), work discipline (X2), quality of work life (X3) and work engagement (X4). While the remaining 5.4% is explained by other factors not examined in this study.